Mimics of tramadol on hypothalamus and liver – a probiotic drug therapy - VENKATA PRASAD CH,; CHANDRASEKHAR K,; PRAMODA KUMARI J, (International Journal of Pharma and Bio Sciences, 2016)
The present paper reveals to assess the mimics of induced toxicity profiles of Tramadol (capsule) and its effects on hypothalamus and liver by treatment of probiotic drug therapy and focus the therapeutic use of probiotics in the modern world. Tramadol, a widely used opioid in recent years, is an effective analgesic agent for the treatment of moderately severe acute or chronic pain. Its analgesic effect is seen in Hypothalamus as a result of its dual mechanism of action, that is, as a re-uptake inhibitor of norepinephrine and serotonin and agonist of the μ-opioid receptor. It is converted in the liver to O-desmethyl-tramadol, which itself is an active substance and 2 to 4 times more potent than tramadol and remaining is excreted by the kidneys. By using probiotic microorganisms drug therapy, the toxicity of tramadol to be controlled or to be reduced.